Silver recovery aqueous techniques from diverse sources: Hydrometallurgy in recycling. (April 2016) - Syed, S.
Highlights: The main impression of this work was to draw attention to the most advance technologies in silver recovery and recycling from various sources. The state of the art in recovery of silver from different sources by hydrometallurgical and bio-metallurgical processing and varieties of leaching, cementing, reducing agents, peeling, electro-coagulants, adsorbents, electro-dialysis, solvents extraction, ionexchange resins and bio-sorbents are highlighted in this article. Economic viability and environmental impact was made in this amendment and silver ion toxicity is highlighted. Abstract: The demand of silver is ever increasing with the advance of the industrialized world, whereas worldwide reserves of high grade silver ores are retreating. However, there exist large stashes of low and lean grade silver ores that are yet to be exploited. The main impression of this work was to draw attention to the most advance technologies in silver recovery and recycling from various sources. The state of the art in recovery of silver from different sources by hydrometallurgical and bio-metallurgical processing and varieties of leaching, cementing, reducing agents, peeling, electro-coagulants, adsorbents, electro-dialysis, solvent extraction, ion exchange resins and bio sorbents are highlighted in this article. It is shown that the major economic driver for recycling of depleted sources is for the recovery of silver. In order to develop an nature-friendly technique for the recovery of silver from diverse sources, a critical comparison of existing technologies is analyzed for both economic viability and environmental impact was made in this amendment and silver ion toxicity is highlighted.